2013
DOI: 10.1063/1.4799650
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of droplet jumping phenomenon with lattice Boltzmann simulation of droplet coalescence

Abstract: Droplet jumping from condensing surfaces induced by droplet coalescence during dropwise condensation of mixed steam on a superhydrophobic surface can significantly enhance condensation heat transfer of mixed steam with non-condensable gas. This phenomenon was visually observed and theoretically analyzed in the present paper. The dynamic evolution of droplet and the velocity distribution inside the droplet during coalescence were simulated using multiphase lattice Boltzmann method. The energy distribution relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 16 publications
2
95
1
Order By: Relevance
“…However, the experimental velocities of the self-jumped microdrops are apparently smaller than their theoretical values. Later, researchers noted that the energy dissipation caused by viscous flow (E vis ) and interface adhesion (E int ) must be considered, [31,[56][57][58][59][60] while gravi tational potential energy may be neglected due to microdrop sizes that are far smaller than the capillary length. Very recently, our group further found that, besides the solid-liquid van der Waals attraction, nanoscale line tension at three-phase contact lines cannot be neglected in calculating adhesioninduced dissipation.…”
Section: Cmdsp Mechanismmentioning
confidence: 99%
“…However, the experimental velocities of the self-jumped microdrops are apparently smaller than their theoretical values. Later, researchers noted that the energy dissipation caused by viscous flow (E vis ) and interface adhesion (E int ) must be considered, [31,[56][57][58][59][60] while gravi tational potential energy may be neglected due to microdrop sizes that are far smaller than the capillary length. Very recently, our group further found that, besides the solid-liquid van der Waals attraction, nanoscale line tension at three-phase contact lines cannot be neglected in calculating adhesioninduced dissipation.…”
Section: Cmdsp Mechanismmentioning
confidence: 99%
“…If the shape and the wettability property of the textured surface are designed properly, the coalesced droplet can not only jump from the textured surface easily but also enhance the heat transfer performance, which is widely used in the applications of self-cleaning, microfluidics, and lab-on-chip devices. Recently, more and more studies have been focusing on the spontaneous jumping of coalesced droplet on superhydrophobic surfaces during dropwise condensation [2,3]. Peng et al [3] experimentally observed the properties of the coalesced droplet induced by the coalescence of two droplets with the same volume and used the two-dimensional free energy lattice Boltzmann model to simulate the droplet coalescence process.…”
Section: Introductionmentioning
confidence: 99%
“…Coalescence-induced jumping phenomena occur on superhydrophobic surfaces but within a small range of initial droplet radii. Recent interest in these phenomena has led to the influence of the droplets radii on the resulting jumping velocity to be explored [3,[8][9][10][11][12]. However, previous analysis on coalescence-induced jumping droplets focused only a limited range of contact angles and droplet radius [10][11][12].…”
Section: Introductionmentioning
confidence: 99%